On 3-topological version of θ-regularity - Martin M. Kovár (International Journal of Mathematics and Mathematical Sciences)
We modify the concept of θ-regularity for spaces with 2 and 3 topologies. The new, more general property is fully preserved by sums and products. Using some bitopological reductions of this property, Michael's theorem for several variants of bitopological paracompactness is proved.